Karakterisasi Kandungan Asam Lemak Beberapa Genotipe Kacang Tanah - Trustinah, Trustinah; Kasno, A. (Jurnal Penelitian Pertanian Tanaman Pangan, 2012)
Groundnut is an economically important oil crop. Main fatty acid components of the groundnut oil are oleic and linoleic acid, which are useful to human health. Forty five groundnut genotypes were grown at the Jambegede Experimental Farm, Malang, East Java during the dry season of 2009. Samples of the harvested grains were analyzed for their fatty acid contents at the Food and Technology Laboratory, Gajah Mada University, Yogyakarta in 2009 using gas chromatography. Groundnut cultivar Singa produced the highest pod yield (3.59 t/ha), followed by cultivars Talam 1 and Gajah (3.10 t/ha). Fatty acid composition among genotypes varied, ranging from 37.7 to 45.7%. Oleic and linoleic acids were the major fatty acid components, accounting for 70.8-85.4% of the total fatty acid contents. The average of oleic, linoleic, palmitic, behenic, and arachidic acid contents was each 37.7%, 41.2%, 12.5%, 3.6%, and 3.0%, respectively. Genotype MLGA 0261 contained the highest oleic acid (49.3%), while MLGA 0077 contained the highest linoleic acid (48.9%). Significant negative correlation between oleic acid content with linoleic acid (-0.59**), palmitic acid (-0.49**), and behenic acid (-0.45**) was detected. These correlations indicated that high content of oleic acid would be followed by low linoleic, palmitic, and behenic acids. Based on the fatty acid content, the groundnut genotypes were divided into three groups. Group I contained palmitic, linoleic, and behenic acids above the average. Group II contained oleic and arachidic acids below the average, and Group III contained high oleic acid and low other fatty acids. Cultivars Gajah, Tapir, Turangga, Sima, Singa, Zebra, Panter, Tuban, and Talam 1 were belong to Group I, where as cultivars Badak, Landak, Jerapah, and Kancil were in the Group II, and MLGA 0261 in Group III.